ETHICAL ISSUES OF PLASTIC SURGERY - Xasanov Azim Mansurovich; Djumayev Akbar Anvarovich (KONFERENSIYALAR, 2025)
Аnnotation. Each epoch set its own priorities regarding the value of the "inner" (soul, consciousness) and "outer" (bodily) in a person, and gave the corporeality itself outlines consistent with the norms of beauty transmitted by culture and perceived by the subject.